Emma Stibbon - melting ice, rising tides - Fisher, Richard (Royal Academy of Arts, 2024)
Emma Stibbon RA depicts landscapes that are undergoing dynamic transformation as a result of climate change. Published to accompany an exhibition at Towner Eastbourne (9 May – 15 September 2024), this beautiful monograph presents many new works and includes a preface by Caroline Lucas MP, an engaging interview with the artist by Sara Cooper and an essay on the sublimity of landscape by Richard Fisher. Tucked inside the back cover is a large poster of Stibbon’s installation Cliff Fall, 2024, first shown at the exhibition
Impressum: First published on the occasion of the exhibition "Emma Stibbon, Melting Ice | Rising Tides", 9 May - 15 September 2024
Beilage: Poster der Installation "Cliff Fall" (2024)
Keywords: Stibbon, Emma -- 1962-; Geschichte 2023; Meer -- Motiv; Klimaänderung -- Motiv; Tiefdruck; Eisberg -- Motiv; Arbeiten auf Papier; Ausstellungskatalog -- Towner Eastbourne -- 09.05.2024-15.09.2024 -- Eastbourne; Bildband